Dylematy rozwoju zrównoważonej produkcji rolniczej na obszarach górzystych - Musiał, Wiesław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The article addresses the problem of sustainable development in agriculture in mountain areas. Against the background of indicated necessities of implementing the laws of sustainable development, the author discussed contemporary dilemmas of mountain agriculture. These comprise depopulation and dezagrarization including fallowing and setting aside of agricultural lands and sub-regional deficiency of grass eating livestock. These phenomena not only weaken the regional economics but also cause negative ecological outcomes. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 164-170